The injection of a screw dislocation into a crystal: Atomistics vs. continuum elastodynamics. (January 2017) - Verschueren, J.; Gurrutxaga-Lerma, B.; Balint, D.S.; Dini, D.; Sutton, A.P.
Abstract: The injection (creation) process of a straight screw dislocation is compared atomistically with elastodynamic continuum theory. A method for injecting quiescent screw dislocations into a crystal of tungsten is simulated using non-equilibrium molecular dynamics. The resulting stress fields are compared to the those of elastodynamic solutions for the injection of a quiescent screw dislocation. A number of differences are found: a plane wave emission is observed to emanate from the whole surface of the cut used to create the dislocation, affecting the displacement field along the dislocation line ( z ), and introducing displacement field components perpendicular to the line (along x and y ). It is argued that, in part, this emission is the result of the finite time required to inject the dislocation, whereby the atoms in the cut surface must temporarily be displaced to unstable positions in order to produce the required slip. By modelling this process in the continuum it is shown that the displacements components normal to the dislocation line arise from transient displacements of atoms in the cut surface parallel to x and y . It is shown that once these displacements are included in the elastodynamic continuum formulation the plane wave emission in u z is correctly captured. A detailed comparison between the atomistic and continuum models is then offered, showing that the main atomistic features can also be captured in the continuum. Abstract : Highlights: A methodology for injecting edge and screw dislocations in an atomistic (molecular dynamics) setting is developed. Core effects hitherto unreported in the literature (emissions from the cut surface, out-of-plane effects). An elastodynamic interpretation of the injection process is developed.